Myelodysplastic Syndrome, Unclassifiable (MDS-U) With 1% Blasts Is a Distinct Subgroup of MDS-U With a Poor Prognosis. Issue 1 (13th June 2017) - Margolskee, Elizabeth; Hasserjian, Robert P.; Hassane, Duane; Tam, Wayne; Mathew, Susan; Ok, Chi Young; Wang, Sa A.; Oak, Jean; Arber, Daniel A.; Orazi, Attilio
Abstract: Objectives: Three situations qualify as myelodysplastic syndrome, unclassifiable (MDS-U): (1) refractory cytopenia with dysplasia and 1% blasts in peripheral blood (BL), (2) pancytopenia with unilineage dysplasia (Pan), and (3) persistent cytopenia, less than 5% bone marrow blasts, and less than 10% dysplastic cells and presence of MDS-defining cytogenetic abnormalities (CG). We compared the clinicopathologic features and mutational profiles for these three groups. Methods: MDS-U cases were reviewed at four major academic institutions. Targeted next-generation sequencing for genes implicated in myeloid neoplasms was performed in a subset of cases. Results: Twenty-seven patients were identified (six MDS-U BL, 13 MDS-U Pan, and eight MDS-U CG). Clonal cytogenetic abnormalities were found in six of six, seven of 13, and eight of eight cases in MDS-U BL, Pan, and CG, respectively ( P > .05). Overall, four of six patients with MDS-U BL progressed to acute myeloid leukemia; no MDS-U Pan or CG patients did. The rates of progression-free survival and mortality (overall survival) were significantly higher in MDS-U BL compared with Pan and CG ( P < .001 for both). Conclusions: We find that MDS-U BL is a distinct subset of MDS-U with a poor prognosis, while MDS-U Pan and CG are relatively indolent. Evaluation of peripheral blood smears in patients with MDS is essential for accurate classification and prognosis.